Industry 4.0 Challenges to the Education System in the Eurasian Economic Union: Possible Changes in Competence Building - Anna SHEVYAKOVA; Elena PETRENKO; Igor DENISOV (Communications of International Proceedings, 2021)
The article reveals the possible changes and requirements for educational institutions imposed by the entry of the world economy into the fourth industrial revolution and Industry 4.0 on the competences of the participants. Industry 4.0 promises new requirements for all participants. Digital formats and learning methods can and/or must be selectively combined with classical forms of learning (seminars, workshops or pedagogical discussions). Innovative teaching-learning solutions offer new opportunities for targeted, individual development of digital competencies. The article systematises institution-specific changes influenced by Industry 4.0 and proposes an author's implementation roadmap for competence development in Industry 4.0 and provides recommendations for educational institutions in the countries belonging to the Eurasian Economic Union (hereafter EAEU) on this basis.
Keywords: Eurasian Economic Union; Industry 4.0; competence; roadmap; fourth industrial revolution; digitalisation; educational institutions.